Milk Pasteurization Machine for the Farmers Group Association of Sido Makmur, Sidorejo, Gunungpati, Semarang City - Setiawan, Florentinus Budi; Lindayani; Sitinjak, Elizabeth Lucky Maretha; Matitaputty, Shandy Jannifer (Journal of Innovation and Community Engagement, 2022)
The Sido Makmur Farmers' Association Sidorejo, Gunungpati, Semarang City has promising potential to become a tourist village based on cow's milk. The problem is that the management of cow's milk products is not optimal because it is still done in a conventional way and does not pay attention to hygiene and sanitation. Until 2020, the Sido Makmur Sidorejo livestock farmer group continues to strive to increase cow's milk products. Therefore, the community service team assists in the safety of dairy cow's milk to be safe from biological, chemical and physical contamination by testing cow's milk in accordance with the Indonesian National Standard Source: SNI 01-3141-1998 (SNI Fresh Cow Milk). The service team also provides assistance in the development of dairy cow's milk products, especially during the fasting month, when demand decreases, overproduction occurs so that at that time cow's milk can still be processed to produce products that can be offered to visitors. In this service activity, the team designed and built a Pasteurization machine with a milk capacity of 15 liters. Based on the results of the experiments carried out, the system can process temperatures between 60OC and 80OC in accordance with the provisions for Pasteurization at medium temperatures.